Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd004437.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic therapy for pulmonary embolism

Abstract: Based on the limited evidence found we cannot conclude whether thrombolytic therapy is better than heparin for pulmonary embolism. More double-blind RCTs, with subgroup analysis of patients presenting with haemodynamically stable acute pulmonary embolism compared to those patients with a haemodynamic unstable condition, are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(20 citation statements)
references
References 45 publications
0
18
0
2
Order By: Relevance
“…Therefore, these authors 50 recommend use of a thrombolytic agent in patients with a major pulmonary embolism and hemodynamic compromise. Dong et al 51 did not find any benefit of thrombolysis or any difference in hemorrhagic events between control and interventional groups. They concluded that evidence of any benefit from the use of thrombolytic agents rather than heparin in the treatment of acute pulmonary embolism is insufficient.…”
Section: Use Of Alteplase In Patients Withmentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, these authors 50 recommend use of a thrombolytic agent in patients with a major pulmonary embolism and hemodynamic compromise. Dong et al 51 did not find any benefit of thrombolysis or any difference in hemorrhagic events between control and interventional groups. They concluded that evidence of any benefit from the use of thrombolytic agents rather than heparin in the treatment of acute pulmonary embolism is insufficient.…”
Section: Use Of Alteplase In Patients Withmentioning
confidence: 88%
“…Currently, 3 meta-analyses [49][50][51] (Table 9) have been conducted to evaluate thrombolysis for the treatment of pulmonary embolism. Agnelli et al 49 found a lower composite end point of death and recurrence of embolism with thrombolysis than with heparin therapy alone.…”
Section: Use Of Alteplase In Patients Withmentioning
confidence: 99%
“…Eine Thrombolyse zeigt im unselektionierten Patientenkollektiv mit Lungenarterienembolie keine Vorteile im Vergleich zur Antikoagulation [17,19,78]. Auch für die Patientengruppe mit mittlerem Risiko wurde der Beleg eines therapeutischen Benefits durch die Thrombolyse bislang nicht erbracht [72].…”
Section: Nicht-hochrisiko-gruppeunclassified
“…Zweifellos erhöht der Nachweis einer TVT die Wahrscheinlichkeit einer PE, aber dies sollte auf keinen Fall dazu führen auf einen diagnostischen Nachweis einer PE leichtfertig oder gar aus ökonomischen Gründen zu verzichten, da auch der Schweregrad der PE ggf. zu therapeutischen Konsequenzen führt [45,46]. Zudem kann in nur 50 % der Patienten mit nachgewiesener PE auch eine TVT nachgewiesen werden kann [47].…”
Section: Kompressionssonographie (Cus)unclassified